Some generalizations of operator inequalities for positive linear maps - Jianming Xue; Xingkai Hu (Journal of Inequalities and Applications, 2016)
Abstract In this paper, we generalize some operator inequalities for positive linear maps due to Lin (Stud. Math. 215:187-194, 2013) and Zhang (Banach J. Math. Anal. 9:166-172, 2015).